Psychological risk and protective factors associated with depression among older adults in mainland China: A systematic review and meta‐analysis. (14th October 2021) - Tang, Tan; Jiang, Jianling; Tang, Xinfeng
Abstract: Background: Although geriatric depression is a public health concern in mainland China, findings about its psychological risk and protective factors have been inconsistent, and its prevention programmes have been deficient. To improve interventions for geriatric depression, we designed a study to systematically estimate the effect size of those factors. Methods: To identify psychological risk and protective factors of geriatric depression, we conducted two independent literature searches in English‐ and Chinese‐language databases, and we used a random effects model to analyse effect sizes. Results: We identified 15 psychological risk and protective factors in 66 studies. The pooled effect sizes between the factors and geriatric depression ranged from 0.129 to 0.567. Self‐esteem displayed a large effect size with depression ( r  = −0.567), whereas medium‐to‐large effect sizes emerged between geriatric depression and negative perceptions of age ( r  = 0.452), resilience ( r  = −0.426), rumination ( r  = 0.432), neuroticism ( r  = 0.381), extraversion ( r  = −0.363), self‐efficacy ( r  = −0.357), sense of control ( r  = −0.343), and negative coping strategies ( r  = 0.315). The sample's mean age, the percentage of women sampled, and the research quality of the studies significantly moderated certain associations. Limitations: Large heterogeneity, the inexplicability of causal relationships between the factors and geriatric depression, and the lack of generalisability to special groups limit our findings. Conclusions: Self‐esteem and perceptions of age are potential targets for improving interventions for geriatric depression in mainland China, which should continue to be developed and assessed for their effectiveness. Key points: It is the first meta‐analysis and systematic review concerning psychological factors of geriatric depression in China. The results show that self‐esteem and ageing perception play a crucial role on geriatric depression. The review has implications for prevention and intervention programs.